2012
DOI: 10.1039/c2jm32500d
|View full text |Cite
|
Sign up to set email alerts
|

Graphite oxide, graphene, and metal-loaded graphene for fire safety applications of polystyrene

Abstract: Graphite oxide, graphene, ZrO 2 -loaded graphene and b-Ni(OH) 2 -loaded graphene (joint appellation: Gs) were prepared and incorporated into polystyrene so as to improve the fire safety properties of polystyrene. By the masterbatch-melt blending technique, Gs nanolayers were well dispersed and exfoliated in polystyrene as thin layers (thickness 0.7-2 nm). The fire safety properties were visibly improved, including an increased thermal degradation temperature (18 C, PS/Ni-Gr-2), decreased peak heat release rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
92
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 63 publications
5
92
0
Order By: Relevance
“…Therefore, to improve flame retardant efficiency of bare graphene seems to be an appealing and challenging work. In our previous work, functionalizing graphene with polyhedral oligomeric silsesquioxan (OapPOSS) 12 and loading transition metal oxides, 13 layered double hydroxides (LDHs), 14 etc. on the surface of graphene are two valid way to improve flame retardant efficiency of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve flame retardant efficiency of bare graphene seems to be an appealing and challenging work. In our previous work, functionalizing graphene with polyhedral oligomeric silsesquioxan (OapPOSS) 12 and loading transition metal oxides, 13 layered double hydroxides (LDHs), 14 etc. on the surface of graphene are two valid way to improve flame retardant efficiency of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…27 Since the heat exchange applications often require the unit to be in close proximity to electronic components or open flame, the materials must also be flame resistant. Several groups have shown that Polystryene (PS) 28 and…”
mentioning
confidence: 99%
“…However, the lower density, high surface area, and the very high aspect ratio attracted much attention to graphene [10] as a candidate for enhancing the corrosion protection property of epoxy. Graphene nanosheets, graphene nanoplatelets and functionalized graphene are different forms of graphene that have been utilized as fillers in various polymeric matrices to enhance their mechanical, thermal, dielectric, gas barrier, and corrosion resistance properties [11][12][13][14][15][16][17][18][19][20][21][22]. The incorporation of graphene into the epoxy matrix is expected to prolong the pathway corrosive agents follow to reach the metal substrate.…”
Section: Introductionmentioning
confidence: 99%